A comparative numerical study of forged bi-metal gears: Bending strength and dynamic response. (November 2019) - Yılmaz, Tufan G.; Doğan, Oğuz; Karpat, Fatih
Highlights: FEA were conducted to obtain root stress and tooth deflection. Weight benefit factor were specified by root stress and weight values. TVMS of bimetallic spur gears with symmetric and asymmetric tooth were calculated. 2DOF dynamic model was used to obtain maximum dynamic factor and STE. Abstract: In this paper, an evaluation of the static and dynamic behavior of bimetallic spur gears with different gear parameters is performed numerically. Bimetallic lightweight spur gears working without a decrease in the performance of the gear mechanisms have many potential benefits in automotive and aerospace applications. A bimetallic spur gear consists of two metals which are steel on the gear teeth and aluminum on the hub region. The dynamic performance of these gears is evaluated by using a two degree of freedom (2-DOF) dynamic model. The finite element method is used to calculate maximum root stress for varying ring thicknesses and other gear parameters for gears with symmetric and asymmetric teeth. These stress values and the weight reduction ratios are taken into consideration to optimize the ring thickness. Tooth deflection is also calculated to determine tooth stiffness by finite element analysis (FEA). Dynamic simulations are carried out to investigate the effects of gear parameters on the dynamic force and static transmission error (STE). Sample simulation results are illustrated with numerical examples. The results indicate that, if properly designed, bimetallic gears can provide a high potential to reduce the weight in power transmission systems without adverse effects on stress and dynamic behavior.